Polycystic Ovary Syndrome and Insulin Resistance: Comparative Analysis of Obese and Non-Obese Women in a Tertiary Care Setting Pakistan: Polycystic Ovary Syndrome and Insulin Resistance: Obese and Non-Obese Women - Gul, Zara; Waheed, Gulfreen (Pakistan Journal of Health Sciences, 2025)
Polycystic ovarian syndrome is a widespread endocrine disease that is linked to insulin resistance, regardless of obesity. This correlation is especially pertinent to South-Asian groups, where culture and lifestyles could mediate the manifestation of diseases. Objectives: To evaluate the effect of obesity on insulin resistance in women with polycystic ovarian syndrome in a tertiary care setting in Lahore, Pakistan. Methods: An analytical cross-sectional study performed at Avicenna Hospital from May to December 2023. The sample size included 220 women with PCOS, with an equal number of obese and non-obese women. BMI, waist circumference, fasting glucose, and insulin level were measured as clinical and metabolic parameters. IR was assessed on the HOMA-IR with a cut-off of 2.5. Data were analyzed with logistic regression and associated statistical t-tests. All subjects gave written consent before the data collection. Results: Obese women had a much greater BMI, waist circumference, glucose, insulin, and HOMAIR scores (p=0.001). The prevalence of IR was 78% compared to 43% among the obese female versus the non-obese female. BMI was found to predict IR (OR over 3.4 with 95% interval in 2.1-5.5) and fasting glucose (OR over 1.5 with 95% interval in 1.1-2.3). The women were also obese and had an unfavorable lipid profile. Conclusions: Insulin resistance is common in both obese and non-obese women with polycystic ovarian syndrome, but it is higher in the obese group.